2014
DOI: 10.1093/ndt/gfu056
|View full text |Cite
|
Sign up to set email alerts
|

Protein intake and kidney function in the middle-age population: contrast between cross-sectional and longitudinal data

Abstract: In middle-aged adults, high protein intake is associated cross-sectionally with higher GFR but longitudinally with greater GFR decline over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 27 publications
3
62
0
Order By: Relevance
“…16 The quoted experimental findings are strongly supported by a recently published Italian 12-year observational study of 1,144 middle-aged adults. 17 In that study, Cirillo et al demonstrated a highly significant positive correlation between protein intake and estimated GFR (eGFR) at baseline, but also a highly significant inverse relationship between baseline protein intake and the 12-year decline in eGFR. Two other large observational studies were unable to identify any effect of protein intake on baseline and subsequent eGFR changes in healthy adults, however.…”
Section: Hyperfiltration and Renal Damagementioning
confidence: 94%
“…16 The quoted experimental findings are strongly supported by a recently published Italian 12-year observational study of 1,144 middle-aged adults. 17 In that study, Cirillo et al demonstrated a highly significant positive correlation between protein intake and estimated GFR (eGFR) at baseline, but also a highly significant inverse relationship between baseline protein intake and the 12-year decline in eGFR. Two other large observational studies were unable to identify any effect of protein intake on baseline and subsequent eGFR changes in healthy adults, however.…”
Section: Hyperfiltration and Renal Damagementioning
confidence: 94%
“…There are additional studies with conflicting results for the impact of high protein diet on renal function decline in the general population. [12,13]…”
Section: Impact Of High Protein Diet On Renal Functionmentioning
confidence: 99%
“…The relationship between dietary protein and DKD is less definitive with regard to the effects of the amount and source of protein on kidney outcomes, and specifically on preventing and impeding the progression of DKD. It is well accepted that excessive dietary protein intake is associated with a worsening of kidney function, increased albuminuria, and CVD mortality ( 10 14 ).…”
Section: Dietary Protein and Dkdmentioning
confidence: 99%